THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND FINANCIAL LITERACY OF THE DEVELOPMENT ON MICRO ENTERPRISES IN DEPOK CITY, PANCORAN MAS DISTRICT - Hani Musyaroh, Kania; Suparno, Suparno; Lestari, Fitra Dila (Universitas Serambi Mekkah, 2024)
The problem of unemployment is still a major concern. The sustainability of MSMEs is an important step in overcoming the problem of unemployment and supporting the national economy. Depok City Pancoran Mas District still has problems and challenges in developing its business, especially in terms of marketing, capital, and human resource governance. One internal factor that requires knowledge and management skills is about human resources. Human resource development is an effort of many parties to help business development. This is mostly done through increasing knowledge in the fields of marketing, production techniques, and financial management. This research was conducted to determine the effect of entrepreneurial education on business development and financial literacy as a mediation on business development. This study uses a quantitative approach that is causual/associative. The sample in this study was 100 micro businesses using Slovin calculations. Data collection techniques using survey methods through the distribution of questionnaires or questionnaires. The analysis used is a descriptive analysis and sturcultural equation modeling technique based on Partial Least Square (SEM-PLS). The results of this study were obtained that: a) Entrepreneurship education has a significant effect on business development, b) Entrepreneurial education has a significant effect on financial literacy, c) Financial literacy has a significant effect on business development, and d) Financial literacy mediates the indirect effects of entrepreneurship education on business development. For further research it is recommended to expand the object of research not only micro businesses but small and medium businesses and expand the research area or sample. Small and medium businesses and expand the research area or sample.